Effect of Directional Hydrogen Bonding on the Self‐Assembly of Anisotropically‐Shaped Macroions. Issue 14 (14th September 2016) - Haso, Fadi; Luo, Jiancheng; Bassil, Bassem S.; Artetxe, Beñat; Zhou, Jing; Yin, Panchao; Reinoso, Santiago; Gutiérrez‐Zorrilla, Juan M.; Kortz, Ulrich; Liu, Tianbo
Abstract: The two polyoxometalate salts K9 LiNa[Fe16 O2 (OH)23 (H2 O)9 (P8 W49 O189 )Gd4 (H2 O)20 ] and Na22 [(2, 3‐pyzdc)2 {NaNi2 (H2 O)4 Sb2 W20 O70 }2 ] (2, 3‐pyzdc: 2, 3‐pyrazinedicarboxylate) demonstrate macroionic self‐assembly phenomenon in dilute solution, but with the trends of assembly size vs. solvent polarity opposite to what has been reported to date. This reveals the influence of additional, directional attractive forces beyond conventional counterion‐mediated attraction. The fact that the size of the assemblies decreases with increasing acetone content in acetone/water mixed solvents is shown to be due to hydrogen bonding. The role of hydrogen bonding is further demonstrated by changes of the assembly size with temperature. In the presence of a hydrogen bond‐cutting solvent such as hexafluoroisopropanol, the counterion‐mediated attraction becomes the dominant driving force and the trend of the assembly size vs. solvent polarity reverts back to the usual charge‐regulated process. Abstract : The presence of directional hydrogen bonding reverses the trend for the usual charge‐regulated self‐assembly process of macroions in solution.